Vitamin D Supplementation in Selected Autoimmune Diseases - Kamińska, Monika; Kozioł, Aleksandra; Miernik-Skrzypczak, Magdalena Agata; Dąbrowska, Natalia; Uchto, Adrian; Karnas-Bogacka, Patrycja; Malicka, Marta Katarzyna; Jasiewicz, Maria; Moczyróg, Katarzyna (Quality in Sport, 2024)
Introduction and Objective. In recent years, awareness of the problem of vitamin D deficiency in the human body has been steadily increasing. There is a growing emphasis on investigating the effects of vitamin D supplementation both in the prevention of autoimmune diseases and in the course of existing diseases. The aim of this study is to highlight and discuss the role of vitamin D supplementation in selected autoimmune diseases. Review methods. The publication is a narrative review. The PubMed electronic database was used to review the literature. To ensure the highest substantive value, the focus was mainly on studies from the last 8 years, with only 6 studies published before 2016, concerning autoimmune diseases. Results. There are still lots of unknowns when it comes to physiology and the role that vitamin D plays in our body and deepening the knowledge of its functions would definitely help prevent many diseases concerning various systems such as musculoskeletal, immune and nervous systems. Wide range of studies have already proven that appropriate supplementation of vitamin D prevents complications and exacerbations of disorders like rheumatoid arthritis, Hashimoto’s thyroiditis, ulcerative colitis, type 1 diabetes and multiple sclerosis. Unfortunately there is no unambiguous evidence of noticeable improvement in the patients suffering from psoriasis after taking vitamin D. There is a huge need for developing guidelines which would establish specific supplementation protocols considering various factors since it is inexplicably difficult to obtain an optimal level of vitamin D in our body. Summary. The increasing prevalence of autoimmune diseases in the population, their coexistence with vitamin D deficiency, and the scientifically proven impact of this vitamin on the body imply the need for an in-depth analysis of the relationship between its supplementation and the prevention and modification of the course of autoimmune diseases.